Estimation of best possible solutions for environmental trade-offs in cold supply chain using BWM based ELECTRE-I approach. (11th July 2022) - Kumar, Neeraj; Tyagi, Mohit; Sachdeva, Anish
Present research work aimed to establish an environmental trade-off between energy consumption and product life cycle in cold supply chain (CSC). For the same, the authors have focused on consolidating the various issues liable to a higher rate of negative emissions from the cold chain (CC) and exploring the best-suited alternatives promising to lower the environmental impact of the same. To establish the theoretical framework and ground the empirical aspects of the analysis, the research work recognised the five most influencing environmental criteria of CSC and proposed the six most preferable alternatives to mitigate the negative influence of criteria on the environment. In order to acquire the objective, the best worst method (BWM) and ELECTRE-I approach has been used. The outcomes of the paper highlight that the 'energy consumption' and 'GHG emissions per unit of cooling load' are the two most severe criteria of the CC from an environmental perspective.